Trawler: de novo regulatory motif discovery pipeline for chromatin immunoprecipitation - Ettwiller, Laurence; Ramialison, Mirana; Wittbrodt, Joachim (Nature methods, 2007)
We developed Trawler, the fastest computational pipeline to date, to efficiently discover over-represented motifs in chromatin immunoprecipitation (ChIP) experiments and to predict their functional instances. When we applied Trawler to data from yeast and mammals, 83% of the known binding sites were accurately called, often with other additional binding sites, providing hints of combinatorial input. Newly discovered motifs and their features (identity, conservation, position in sequence) are displayed on a web interface.